Pendidikan Kristiani Mereduksi Hegemoni Politik Identitas: Upaya Membangun Demokrasi dan Kebebasan Berpolitik - Arifianto, Yonatan Alex (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2023)
The phenomenon of identity politics has had a negative impact in the form of social segregation and conflict that has the potential to lead to division. The government urges all parties to maintain the unity and integrity of the nation through various means, one of which is launching a religious mode-ration program several years ago. Religion is considered essential and crucial in the issue of identity politics. This research aims to initiate the role of Christian education in reducing the hegemony of identity politics. By using descriptive analysis methods through literature studies from research results on identity politics and the essence of Christian education, a religious format is produced that can reduce the hegemony of identity politics. In conclusion, Christian education can be a way for the church to build a political paradigm with integrity and a democratic political situation. Abstrak Fenomena politik identitas telah memberikan dampak negatif berupa segregasi sosial hingga konflik yang berpotensi pada perpecahan. Pemerintah mendesak semua pihak agar memelihara kesatuan dan keutuhan bangsa melalui berbagai cara, yang salah satunya adalah meluncurkan program moderasi beragama beberapa tahun lalu. Agama dianggap penting dan krusial dalam perosalan politik identitas. Penelitian ini bertujuan untuk menginisiasi peran pendidikan kristiani dalam mereduksi hegemoni politik identitas. Dengan menggunakan metode analisis deskriptif melalui kajian literatur dari hasil penelitian tentang politik identitas dan esensi pendidikan kristiani, dihasilkan sebuah format beragama yang mampu mereduksi hegemoni politik identitas. Simpulannya, pendidikan kristiani dapat menjadi cara gereja membangun paradigma politik yang berintegritas dan situasi berpolitik yang demokratis.